PENEGAKAN HUKUM TINDAK PIDANA PENIPUAN ONLINE: STUDI IMPLEMENTASI UNDANG-UNDANG ITE DI INDONESIA - Mohammad Daffa Saifullah; Pramono, Agus (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
The increasing prevalence of cybercrime, particularly online fraud, poses significant challenges for modern legal systems. Although a number of studies have highlighted the technological and criminological dimensions of cybercrime, scientific attention to the normative adequacy and effectiveness of the legal framework governing online fraud remains limited. This study fills this gap by examining the interaction between the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE) in regulating online fraud. The research questions addressed in this study are (1) How is online fraud regulated by law and (2) What are the obstacles faced in the process of enforcing the Law on Online Fraud? The research method used in this study is a legal-normative method by analyzing several primary and secondary legal sources, including legislation, journal articles, and electronic news. Based on the research process that has been carried out, it was found that in Indonesia itself, there are already laws that regulate violations committed by individuals/entities in the virtual environment, which are listed in several laws and regulations, both in the ITE Law and the Criminal Code. However, in the implementation process, law enforcement officials still face many obstacles in carrying out their duties in relation to cybercrime cases, one of which is the ambiguity of the choice of law. Keywords: Online Fraud, Cybercrime, Personal Data, ITE Law, Criminal Code